The typology of entrepreneurs among single mothers in Kuching, Sarawak / Nurul Lizzan Kamarudin, Wee Chong Hui and Hasmiza Abdul Majeed - Kamarudin, Nurul Lizzan; Chong Hui, Wee; Abdul Majeed, Hasmiza (Research Management Institute (RMI), 2013)
Urbanization, migration, globalization, and the demand for socio-economic well-being have led to the break-up of families. There are concerns for single mothers in the gender-bias society, and single mothers form a target group of the vulnerable in The Tenth Malaysian Plan (2011-2015). Entrepreneurship has been proposed as a strategy for economic development in general and socio-economic development and self-reliance of the less fortunate in particular. Given the scenario, this study seeks to identify the typology of single mother entrepreneurs in Kuching, Sarawak with respect to social-cultural background, experience and decision making. Data was collected by in-depth interviews of single mother entrepreneur of various ethnicities who ran their businesses in Kuching. The study drew on case studies on these entrepreneurs to explore the relationship between socio-cultural background and entrepreneurial development. It reviewed the experiences of these entrepreneurs within their respective socioeconomic settings. It traced the single mother entrepreneurs' decisions at various stages of their lives in general and business cycles in particular. A number of entrepreneurs interviewed had run their current businesses for at least two years. Some of the entrepreneurs became single mothers before they started their current businesses because of their interest and motivation from family members, friends and other mentor-entrepreneurs. Some entrepreneurs started their businesses after becoming single mothers mainly to be better able to support themselves and their families, especially schooling children. A number of the entrepreneurs with secondary education were better able to access government facilities to develop their businesses. Social networks such as participation in the Sarawak Single Mothers' Association provided entrepreneurial exposure and business contacts to facilitate some entrepreneurial development. Some of the entrepreneurs had businesses which are resilient to economic vulnerabilities, although their businesses provided minimal income. It appears that the various government programmes to support single mother entrepreneurs have to be re-organised for the micro needs of the single mother entrepreneurs and made more accessible to the entrepreneurs.